The Influence of Work Intensification on Employee Performance through Emotional Exhaustion and Technostress - Muhammad Syafri (The Eastasouth Management and Business, 2026)
This study investigates the effect of work intensification on employee performance through the mediating roles of emotional exhaustion and technostress in the Indonesian work context. Rapid organizational changes and increasing reliance on digital technologies have intensified work demands, potentially affecting employees’ psychological well-being and performance. Using a quantitative research design, data were collected from 150 employees in Indonesia through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The results reveal that work intensification has a significant positive effect on emotional exhaustion and technostress. Furthermore, emotional exhaustion and technostress have significant negative effects on employee performance. Mediation analysis indicates that emotional exhaustion and technostress partially mediate the relationship between work intensification and employee performance, with emotional exhaustion showing a stronger mediating effect. These findings highlight that intensified work conditions may undermine employee performance primarily through psychological and technology-related stress. The study contributes to the literature on occupational stress and performance by providing empirical evidence from a developing-country context and offers practical insights for organizations seeking to balance productivity demands with employee well-being.